2006
DOI: 10.1161/01.atv.0000219697.99134.10
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony Stimulating Factor Directly Inhibits Myocardial Ischemia-Reperfusion Injury Through Akt–Endothelial NO Synthase Pathway

Abstract: Objective-Granulocyte colony stimulating factor (G-CSF) has been reported recently to prevent cardiac remodeling and dysfunction after acute myocardial infarction through signal transducer and activator of transcription 3 (STAT3). In this study, we examined acute effects of G-CSF on the heart against ischemia-reperfusion injury. Methods and Results-Rat hearts were subjected to global 35-minute ischemia and 120-minute reperfusion in Langendorff system with or without G-CSF (300 ng/mL). G-CSF administration was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 12 publications
1
42
0
Order By: Relevance
“…Recently, much attention has been paid to the cardioprotective effects of granulocyte colony stimulating factor (G-CSF). The administration of G-CSF preserves myocardium in the myocardial infarction model (11) as well as the I/R model (26). In G-CSF signaling, JAK2/STAT3 pathway has been proposed to be important in antifibrotic effects after myocardial infarction during subacute and chronic phase, whereas the Akt/NOS pathway contributes to the beneficial effect of G-CSF in I/R hearts during the acute phase (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, much attention has been paid to the cardioprotective effects of granulocyte colony stimulating factor (G-CSF). The administration of G-CSF preserves myocardium in the myocardial infarction model (11) as well as the I/R model (26). In G-CSF signaling, JAK2/STAT3 pathway has been proposed to be important in antifibrotic effects after myocardial infarction during subacute and chronic phase, whereas the Akt/NOS pathway contributes to the beneficial effect of G-CSF in I/R hearts during the acute phase (25).…”
Section: Discussionmentioning
confidence: 99%
“…The first possibility was supported by experiments in STAT3 deficient mice, where insulin failed to phosphorylate Akt. Ueda et al [44] recently reported that granulocyte colony stimulating factor (G-CSF) activated JAK-STAT, PI3K and Akt. Use of the JAK2 inhibitor AG490 abrogated G-CSF induced phosphorylation of JAK2, STAT3, Akt; and the PI3K inhibitor LY294002 suppressed G-CSF induced phosphorylation of Akt, but not JAK2 or STAT3.…”
Section: Signalling Pathways Involvedmentioning
confidence: 99%
“…Kazutaka Ueda, 1 MD, Nobuaki Fukuma, 1 MD, and Eiki Takimoto, 1 MD R eperfusion therapy is beneficial to prevent cardiomyocyte death and contractile dysfunction after myocardial infarction. However, numerous studies have shown that reperfusion itself may enhance the injury, resulting in the increase of infarct size after ischemia [ie, ischemiareperfusion (I/R) injury].…”
Section: Hydrogen Sulfide a Potential Cardioprotective Gas Activatinmentioning
confidence: 99%
“…Meanwhile, it has been recently reported that brief intermittent ischemia applied after the onset of reperfusion, termed "postconditioning," reduces myocardial injury to an extent comparable to the reduction by preconditioning. 1) Various cardioprotective mechanisms of postconditioning have been proposed, and pharmacological postconditioning by the administration of agents that modulate these mechanisms seems to be beneficial in I/R injury.…”
Section: Hydrogen Sulfide a Potential Cardioprotective Gas Activatinmentioning
confidence: 99%